Meanings of English Loanwords in Indonesian Articles of Sport - Ari Nurweni (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
This study investigates the meanings of English loanwords in Indonesian sport texts. The data analyzed in this study were taken from sport articles of an Indonesian newspaper in 2010 and 2011. Their meanings in the text were compared to those in English dictionaries, sport glossary and KBBI 2008 using Nida’s componential analysis of meaning (Nida, 1975:32-67). The results showed that most of the English loanwords in the Indonesian sport articles had their meanings unchanged and some others experienced semantic changes. The results imply that some revision should be made to the meanings of some English loanwords in KBBI 2008.